2017
DOI: 10.5539/ass.v13n4p192
|View full text |Cite
|
Sign up to set email alerts
|

The ASEAN Free Trade Agreement and Vietnam’s Trade Efficiency

Abstract: This study employs a stochastic gravity model to estimate the efficiency performance of Vietnam's trade with its main trading partners from 1995-2015. Trade efficiency is measured as the ratio of actual trade volume to the maximum likelihood. Moreover. it analyzes the effects of both natural and man-made trade barriers on trade efficiency. The empirical results suggest that the actual trade of Vietnam appears to be much smaller than a possible efficiency level and that there is large space for further progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Therefore, the composite error term is decomposed into the standard random error term and non-negative term, which captures trade inefficiency. The appearance of the non-negative error means that the actual level of trade is always lower than the potential level of trade because unobserved trade resistances hinder the actual trade from reaching the maximum level (Hai and Thang, 2017). This approach allows for estimating the frontier level of trade in the hypothetical case of no restriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the composite error term is decomposed into the standard random error term and non-negative term, which captures trade inefficiency. The appearance of the non-negative error means that the actual level of trade is always lower than the potential level of trade because unobserved trade resistances hinder the actual trade from reaching the maximum level (Hai and Thang, 2017). This approach allows for estimating the frontier level of trade in the hypothetical case of no restriction.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that membership in ASEAN contributed positively to the country's trade efficiency while rules of origin and non-membership in the EU and NAFTA had a negative impact. Hai and Thang (2017) employed a stochastic gravity model to estimate the efficiency performance of Vietnam's trade with its main trading partners from 1995 to 2015. They found that Vietnam's membership in the ASEAN Free Trade Agreement (FTA) has improved the trade efficiency, whereas tariffs and domestic devaluation have reduced it.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Nguyen and Doan (2017) is the first paper that uses the SFGM to study determinants of Vietnam's trade efficiency. The authors examined Vietnam's trade efficiency with 30 partners (both ASEAN and non-ASEAN) over an 11-year period (1995-2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This challenge arises both from within the country and from abroad. From within the country, there are competitions between the firms the and industries (Nguyen and Doan, 2017). The competition can be in form of price wars, promotions, as well as the quality of after-sales services.…”
Section: Introductionmentioning
confidence: 99%